Comprehensive review of the application of MP and the potential for graft modification - Vargas, Paola A.; Yu, Christine; Goldaracena, Nicolas (Frontiers in Transplantation, 2023)
Following procurement, the liver graft is exposed to an ischemic period that triggers several pathophysiologic changes in response to oxygen deprivation. Therefore, the goal during organ preservation is to attenuate such response and provide an adequate environment that prepares the graft for its metabolic reactivation following implantation. This has been widely achieved via static cold storage preservation, where the maintenance of the graft using cold preservation solutions reduce its metabolic activity and confer cytoprotection until transplantation. However, despite being the gold standard for organ preservation, static cold storage holds several disadvantages. In addition, the ongoing organ shortage has led to the use of unconventional grafts that could benefit from therapies pre-transplant. Organ preservation via machine perfusion systems appears as a promising solution to address both. Here, we aim to present a state-of-the-art review regarding liver graft modification options using machine perfusion systems in combination with adjuvant strategies including immunomodulation, gene therapy and pharmacotherapy. Available reports are scarce and mostly on experimental animal models. Nevertheless, their promising results suggest that organ preservation using machine perfusion system when combined with alternative therapies can be feasible and safe strategies for graft modification. However, further research on clinical settings are needed to better elucidate the true effect of graft modification pre-transplant on short- and long-term graft and patient survival. There is a long way ahead to develop guidelines and approve these novel therapies for clinical practice. However, the path looks promising.